Mudlogging Service Performance Evaluation In Offshore Mahakam: A Case Study on The Consortium Contract Within PT PHM - Rio M A Sitorus; Akbar Adhi Utama (Journal Research of Social Science, Economics, and Management, 2025)
PT Pertamina Hulu Mahakam (PHM) is an oil and gas exploration and production operator in the Mahakam block, East Kalimantan, and conducts drilling operations for development and exploration wells using five offshore rigs. Mudlogging services are crucial for real-time geological monitoring and operational safety in offshore drilling. Mudlogging plays a crucial role in maintaining well integrity and enhancing drilling efficiency. From 2019, these services have been delivered through two major contracts, one awarded to PTGI and the other to a consortium between PTEN and PTGS. However, the second period (2022-2024) saw a sharp decline in performance, resulting in an estimated USD 350,000 in rig standby costs. This research aims to identify the root causes of the decline in mudlogging performance and propose practical improvement strategies to restore operational reliability and minimize non-productive time (NPT). A mixed-method approach was adopted, combining structured interviews with key stakeholders, and Likert-scale questionnaires were collected from the stakeholders and expert. Qualitative data analysis, utilizing root cause methodologies, fishbone diagrams, and current reality trees (CRTs), revealed that the absence of clear governance structures and role clarity led to weak coordination, delayed decisions, ineffective communication, and inadequate technical oversight. Insufficient training, high turnover, and limited motivation among contracted personnel in one of the consortium company were also identified as contributing factors in this research. The analytic hierarchy process (AHP) was applied to prioritize improvement strategies, with restructuring the consortium scoring highest and training enhancement being the most impactful levers for restoring performance.